The role of attachment style and anthropomorphism in predicting hoarding behaviours in a non-clinical sample. (September 2016) - Neave, Nick; Tyson, Hannah; McInnes, Lynn; Hamilton, Colin
Abstract: Hoarding behaviours are characterised by the acquisition of and failure to discard possessions, which leads to excessive and often dangerous clutter and significant psychological/emotional distress. The cognitive behavioural-model posits that a key aspect in the expression of hoarding tendencies is an excessive attachment to objects. Research indicates that attachment style and anthropomorphic tendencies are associated with excessive object attachment and subsequent hoarding. In this study, a non-clinical sample of 283 participants (210 female) completed questionnaires measuring adult attachment styles, attachment to objects, anthropomorphic tendencies, and hoarding severity and behaviours. Females displayed significantly higher scores on hoarding severity, anxious and avoidant attachments, and on anthropomorphism. Strong positive correlations were found between measures of inanimate object attachment, adult attachment style, and anthropomorphism, with hoarding behaviours and cognitions. Subsequent regression analyses revealed that one measure of adult attachment (degree of anxious attachment) and object attachment was significant predictors of hoarding behaviours and cognitions. Highlights: Females showed more hoarding tendencies. Females displayed anxious and avoidant attachment styles, and anthropomorphised more. Hoarding was associated with object attachment, attachment style and anthropomorphism. Attachment to objects significantly predicted hoarding severity and cognitions.